Estimation of the dietary intake and risk assessment of food carcinogens (3-MCPD and 1, 3-DCP) in soy sauces by Monte Carlo simulation. (1st May 2020) - Wong, Siew Fang; Lee, Bai Qin; Low, Kah Hin; Jenatabadi, Hashem Salarzadeh; Wan Mohamed Radzi, Che Wan Jasimah Bt; Khor, Sook Mei
Highlights: 3-MCPD and 1, 3-DCP were found in soy sauces and related products by a GC–MS method. Levels of 3-MCPD in chosen food products varied from not detected to 0.1223 mg kg −1 . All chicken seasoning cubes contained more than 0.02 mg kg −1 of 3-MCPD. Malaysians do not suffer from a potential health risks based on Monte Carlo method. Abstract: Quantifiable levels of 3-chloropropane-1, 2-diol (3-MCPD) and 1, 3-dichloro-2-propanol (1, 3-DCP) were found in domestically manufactured soy-based sauces. Selected commercial foods in the Malaysian market ( n  = 43) were analyzed for their 3-MCPD and 1, 3-DCP contents using a validated gas chromatography–mass spectrometry technique. The 3-MCPD and 1, 3-DCP contents of the analyzed food samples varied from not detectable levels to 0.1223 ± 0.0419 mg kg −1 and not detectable levels to 0.025 ± 0.0041 mg kg −1, respectively. High concentrations of 3-MCPD, exceeding Malaysia's maximum tolerable limit of 0.02 mg kg −1, were found in chicken seasoning cubes (mean = 0.0898 ± 0.0378 mg kg −1 ). Monte Carlo simulation-based health risk assessment revealed that 3-MCPD and 1, 3-DCP intakes in the 50th, 95th, and 99th percentiles were lower than 4 µg kg −1 bw day −1, the limit recommended by JECFA in 2016. Hence, it was concluded that the exposure of Malaysian citizens to chloropropanols through soy sauce consumption does not present a health risk.